Amari and the night brothers - Alston, B. B. (Alston, B. B. Supernatural investigations, 2021)
Thirteen-year-old Amari, a poor Black girl from the projects, gets an invitation from her missing brother to join the Bureau of Supernatural Affairs and join in the fight against an evil magician.